THE INFLUENCE OF THE ENGLISH DAY PROGRAM ON STUDENTS' SPEAKING ABILITY - Atrianus Toni (Pedagogic Research-Applied Literacy Journal, 2026)
Speaking ability is a fundamental component of English language learning; however, many students have limited opportunities to practice speaking in authentic communicative contexts. This study aimed to investigate the influence of the English Day Program on students' speaking ability at the senior high school level. The research employed a quantitative approach using a correlational design. The participants were selected through simple random sampling, and the data were collected using a questionnaire to measure students' participation in the English Day Program and a speaking test to assess their speaking ability. The data were analyzed using descriptive statistics, Pearson Product-Moment correlation, and simple linear regression. The findings revealed that the English Day Program had a significant positive influence on students' speaking ability. Students who actively participated in the program demonstrated higher levels of fluency, pronunciation, vocabulary, grammar, and comprehension than those with lower participation. Therefore, the English Day Program can be considered an effective strategy for improving students' English-speaking ability.